2018
DOI: 10.2355/isijinternational.isijint-2017-552
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Reducibilities of Columnar Silico-ferrite of Calcium and Aluminum (SFCA) Covered with Slag and Acicular SFCA with Fine Pores

Abstract: Reducibilities of silico-ferrite of calcium and aluminum (SFCA) have been examined using high temperature X-ray diffraction (XRD) analysis including the effect of hydrogen. Two types of sample were prepared: columnar SFCA covered with slag and acicular SFCA with fine pores, denoted by 'Columnar SFCA' and 'Acicular SFCA', respectively. These samples were synthesized using chemical reagents and iron ore powders. XRD analysis was applied to the samples heated in a condition simulating a blast furnace. Oxygen part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 17 publications
0
26
0
Order By: Relevance
“…Iron ore sinter remains an important feed for the production of iron and steel, and research continues into the improvement of sinter quality for economic and environmental reasons [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Iron ore sinter remains an important feed for the production of iron and steel, and research continues into the improvement of sinter quality for economic and environmental reasons [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…16 Other work by Mezibricky and Frolichova 7 and Takayama et al 8 has demonstrated that using a morphological approach to distinguishing between SFCA and SFCA-I types is problematic, since both phases can exhibit similar textures. Similarly, Cai et al 9 produced both columnar and acicular (i.e., platy) textures of SFCA in their work, identifying both as SFCA using XRD.…”
Section: Introductionmentioning
confidence: 98%
“…Ó 2020 The Author(s) 1250°C, while SFCA is formed at higher temperatures > 1250-1300°C and may also crystallize from a melt upon cooling. 5,6 SFCA-I is high in iron and low in silica, with approximate composition of 84 wt% Fe 2 O 3,7 wt% CaO, 1 wt% SiO 2 , and 2 wt% Al 2 O 3 11 ; SCFA is low in iron and high in silica, with approximate composition of 60-76 wt% Fe 2 O 3, [7][8][9][10] wt% CaO, 3-10 wt% SiO 2,[4][5][6][11][12][13][14] wt% Al 2 O 3 , and 0.7-1.5 wt% MgO. 1,2,12 Recently Mumme (2003) 13 and Webster et al (2012) 5 have identified additional forms of SFCA, denoted as SFCA-II and Fe-rich SFCA, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…As typical secondary compounds in lime-fluxed iron ore sinters, calcium ferrites and calcium silicates form the sinter matrix. Recent works dealing with the mineralogy of iron ore sinters mostly focus on the complex calcium ferrite phase [10][11][12]. During the ferrite formation process, silica and alumina enter the structure, which results in crystallization of aluminosilicoferrites of calcium (often referred to as SFCA, short for silico-ferrite of calcium and aluminum).…”
Section: Introductionmentioning
confidence: 99%